2020
DOI: 10.1111/sms.13651
|View full text |Cite
|
Sign up to set email alerts
|

Lung function and oxygen saturation after participation in Norseman Xtreme Triathlon

Abstract: Objectives:To examine evidence of exercise-induced bronchoconstriction (EIB) defined as ≥10% reduction in forced expiratory volume in one second (FEV 1 ) and exercise-induced arterial hypoxemia (EIAH) defined as ≥4% reduction in oxygen saturation (SpO 2 ) from before to after participation in the Norseman Xtreme Triathlon. Secondarily, to assess whether changes in FEV 1 and SpO 2 are related to respiratory symptoms, training volume, and race time. Methods: In this quasi-experimental non-controlled study, we in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 45 publications
(117 reference statements)
1
11
0
Order By: Relevance
“…SpO 2 is the physiological parameter which tracks the amount of oxygen dissolved in arterial blood or transported oxygen bound to hemoglobin, as indirectly measured at suitable peripheral sites (i.e., finger, toe, forehead, and ear) by pulse oximetry. Since the brain, as well as the muscles, requires a constant oxygen supply to support the high metabolic rate production necessary to remain electrically active (Williams et al, 2019 ), SpO 2 monitoring is of relevance to detect possible risk conditions not only in clinical settings, but also in physiological studies, sport science, and occupational medicine (Costello et al, 2020 ; Pham et al, 2020 ; Stensrud et al, 2020 ). A reduction in oxygen availability, as experienced at high altitudes or in particular challenging situations, can have a detrimental effect on brain and muscles function, inducing performance decline and increasing the risk of errors and injuries (Hoiland et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…SpO 2 is the physiological parameter which tracks the amount of oxygen dissolved in arterial blood or transported oxygen bound to hemoglobin, as indirectly measured at suitable peripheral sites (i.e., finger, toe, forehead, and ear) by pulse oximetry. Since the brain, as well as the muscles, requires a constant oxygen supply to support the high metabolic rate production necessary to remain electrically active (Williams et al, 2019 ), SpO 2 monitoring is of relevance to detect possible risk conditions not only in clinical settings, but also in physiological studies, sport science, and occupational medicine (Costello et al, 2020 ; Pham et al, 2020 ; Stensrud et al, 2020 ). A reduction in oxygen availability, as experienced at high altitudes or in particular challenging situations, can have a detrimental effect on brain and muscles function, inducing performance decline and increasing the risk of errors and injuries (Hoiland et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…The exact mechanisms that cause exhaustion after prolonged exercise are still not completely elucidated. However several factors have been suggested, such as muscle damage [ 1 , 2 , 3 , 4 , 32 ], inflammation [ 1 , 2 , 3 ], exercise-induced bronchoconstriction [ 33 ], and reduction in essential nutrients [ 5 , 14 , 15 ]. The reduced levels of L-arginine and the L-arginine/ADMA ratio and the increased levels of SDMA observed after strenuous exercise, observed in the present study, may result in a state of reduced NO-synthesis capability.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the missing direct link between respiratory muscle fatigue and lung function in the present study should be interpreted with caution because static measures such as MIP and MEP do not directly reflect changes in the potential to produce high shortening velocities as present during all flow-dependent maneuvers 30 . Additionally or alternatively, the decrement in FVC may also be influenced by other factors such as peripheral airway constriction 4 5 6 . However, in the present study, no significant changes were observed in FEV 1 , PEF, maximal expiratory flow-volume curves at different percentages of FVC (FEF 25 , FEF 50 , FEF 75 and FEF 25–75 ) and in the FEV 1 /FVC and FEV 1 /PEF ratios, suggesting no evidence of lower- or upper-airway obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…From a pulmonary perspective, several studies have reported that endurance athletes -and particularly athletes competing at the higher levels -are more prone to exercise-induced bronchoconstriction or bronchial hyperreactivity [4][5][6]. In adult athletes, the functional capacity of the respiratory system to generate air flow is known to be reduced after mixed-modality long-duration races, i. e. triathlon and wilderness multisport endurance competitive race.…”
Section: Introductionmentioning
confidence: 99%